2015
DOI: 10.1186/s12967-015-0690-y
|View full text |Cite
|
Sign up to set email alerts
|

Short and long term health effects of parental tobacco smoking during pregnancy and lactation: a descriptive review

Abstract: A great deal of attention has been focused on adverse effects of tobacco smoking on conception, pregnancy, fetal, and child health. The aim of this paper is to discuss the current evidence regarding short and long-term health effects on child health of parental smoking during pregnancy and lactation and the potential underlying mechanisms. Studies were searched on MEDLINE® and Cochrane database inserting, individually and using the Boolean ANDs and ORs, ‘pregnancy’, ‘human lactation’, ‘fetal growth’, ‘metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
185
3
21

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(215 citation statements)
references
References 49 publications
6
185
3
21
Order By: Relevance
“…Maternal smoking has consistently been linked to adverse birth and child outcomes ranging from poor fetal growth, low birth weight, stillbirth, sudden unexpected death in infancy and a broad range of birth defects to later childhood behavioural problems, obesity and impaired lung function 98,99 . Heavier antenatal drinking (that is, more than three standard drinks per day) is also independently predictive of poor birth outcomes.…”
Section: Persistence Of Adolescent Assets and Risksmentioning
confidence: 99%
“…Maternal smoking has consistently been linked to adverse birth and child outcomes ranging from poor fetal growth, low birth weight, stillbirth, sudden unexpected death in infancy and a broad range of birth defects to later childhood behavioural problems, obesity and impaired lung function 98,99 . Heavier antenatal drinking (that is, more than three standard drinks per day) is also independently predictive of poor birth outcomes.…”
Section: Persistence Of Adolescent Assets and Risksmentioning
confidence: 99%
“…Cardiovascular disease is the leading cause of death worldwide (Kadhum et al, 2015; Morris et al, 2015). Many studies have reported a strong association between smoking and cardiovascular disease occurrence (Doria et al, 2003; Banderali et al, 2015; Morris et al, 2015; Zaquia Leão et al, 2016). Nevertheless, other studies have failed to find the association between smoking and cardiovascular disease, which is possibly due to the study population and size (Akhtar and Asghar, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Enfin, la prématurité affecte plus de 7% des naissances en France et est en constante augmentation (Valery et al 2015). L'environnement maternel au sens large peut affecter la fonction placentaire et les échanges entre la mère et le foetus et il est bien établi que le tabagisme est une cause majeure de RCIU et de prématurité (Mund et al 2013 ;Banderali et al 2015). Il est assez logique de suspecter un rôle de la pollution atmosphérique dans ces pathologies.…”
Section: Pollution Atmosphérique Et Grossesseunclassified